1970
DOI: 10.1111/j.1471-0528.1970.tb03401.x
|View full text |Cite
|
Sign up to set email alerts
|

THE NATURAL HISTORY OF CERVICAL CARCINOMA IN SITU

Abstract: Of a total of 576 patients with cervical carcinoma in situ, 75 have shown evidence of persistent disease after various initial treatments. None of the 75 have developed invasive cervical cancer during follow-up. This result is used to obtain confidence limits for the probability with which carcinoma in situ will become invasive and for the period after, which it does so. Two separate assumptions about the distribution of latent periods give comparable values for these limits, which imply a low invasive potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Intra-epithelial lesions can be found associated with CC, and are probably the precursors of adjacent invasive lesions. However, the large majority of CINs -even high-grade lesions -spontaneously regress, which indicates that additional events to those observed in the most commonly encountered CINs, which do not evolve into cancer, are required for conversion to malignancy [4].…”
mentioning
confidence: 99%
“…Intra-epithelial lesions can be found associated with CC, and are probably the precursors of adjacent invasive lesions. However, the large majority of CINs -even high-grade lesions -spontaneously regress, which indicates that additional events to those observed in the most commonly encountered CINs, which do not evolve into cancer, are required for conversion to malignancy [4].…”
mentioning
confidence: 99%
“…In 1966 Green gained the approval of the hospital medical committee for a study in which no further treatment would be offered to a group of women in whom a histologic diagnosis of CIS of the cervix had been established by a representative biopsy with minimal disturbance of the lesion. While Green's publications through the 1960s and 1970s 3,4 appeared to confirm his theory, an independent reanalysis of data from the same group of women by McIndoe et al in 1984 demonstrated a 25-fold increased risk of cervical cancer in women with persistent cytologic abnormalities as compared with women with normal cytologic follow-up. 5 We reanalyzed the original material-by reviewing medical records, histopathologic slides and cytology smears-and performed linkages with cancer registries, death registries and electoral rolls primarily to assess, in relation to the women's treatment, the longterm risk of cancer of the lower genital tract in this cohort (McCredie et al, in preparation).…”
mentioning
confidence: 91%
“…Green's study 4 involved withholding definitive treatment from a group of women with a histologic diagnosis of CIN 3 so that he could follow the natural history of the disease. Although many of the women subsequently had positive smears, Green either did no biopsy or performed only inadequate biopsies to check for invasion.…”
Section: Review Of Cytologic Slidesmentioning
confidence: 99%
“…These women were followed up during 13 to 141 months, with a mean of 53 months (4.42 years). None of these women developed invasive cancer during the follow-up period [37]. Interpreting the results from the clinical study by an inappropriate model led Professor Green to dismiss the common opinion that CIS is a pre-stage of cancer and to question the need for any treatment at all of CIS.…”
Section: Pred T T Pred T T Births Tmentioning
confidence: 99%
“…The conceptual description quoted here is taken from [37], but we have changed the denotation of the sojourn time from m to D.…”
Section: Conceptual Modelmentioning
confidence: 99%